Religion and the Individual: Belief, Practice, and Identity - Michael J. Thate (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This Special Issue is both experimental and comparative. It appropriates diverse disciplinary idioms from the distinctive fields our authors inhabit to focus on the ever-recurrent theme of the individual and the study of religion. Here the familiar topics of "belief", "practice" and "identity" come into conversation with each other from scholars in anthropology, sociology, African-American history, Asian religions, philosophy, religious studies, critical theory, and ancient history. This unashamedly eclectic venture demonstrates both the remarkable diversity enacted by the signifier, "religious", and the dynamic potential of conversation between interesting scholars working on remarkably interesting topics.